Rsg1.a3: A new allele conferring unique resistance to greenbug Biotype H at the Rsg1 locus in Hordeum vulgare ssp. spontaneum. Issue 5 (4th August 2021) - Xu, Xiangyang; Mornhinweg, Dolores W.; Bai, Guihua; Steffenson, Brian; Bian, Ruolin; Li, Genqiao; Bernardo, Amy
Abstract: Greenbug ( Schizaphisgraminum Rondani) is one of the aphids causing significant cereal yield losses worldwide, and greenbug Biotype H is virulent to all known greenbug resistance genes in barley ( Hordeum L.). Wild barley ( Hordeum vulgare ssp. spontaneum ) accession WBDC336 (PI 682028) exhibits resistance to greenbug Biotypes C, E, H, I, WY81, WY12 MC, and WY86. To investigate the genetics of greenbug resistance in WBDC336, a recombinant inbred line (RIL) population was developed from the cross Weskan × WBDC336. The RIL population was evaluated for responses to greenbug Biotype E and genotyped using genotyping‐by‐sequencing. Among 67, 238 single nucleotide polymorphisms (SNPs) identified, 3, 907 high quality SNPs were selected for gene mapping after several filtering steps. Linkage analysis positioned the greenbug resistance gene to a 1.14‐Mb interval in the terminal region of the long arm of chromosome 3H in WBDC336, where the greenbug resistance gene Rsg1 resides. Greenbug assays and an allelism test indicated that the greenbug resistance gene in WBDC336 is likely an allele at the Rsg1 locus and was given the allele designation Rsg1.a3 . Two Kompetitive allele‐specific polymerase chain reaction (KASP) markers were developed from SNPs closely linked to Rsg1.a3, and these markers can be used to tag both alleles at the Rsg1 locus in breeding program utilizing marker‐assisted selection. Core Ideas: The first barley gene conferring resistance to greenbug Biotype H was identified in WBDC366. The greenbug resistance gene in WBDC366, designated Rsg1.a3, is likely allelic to Rsg1 . Two KASP markers closely linked to Rsg1.a3 were developed for marker‐assisted selection.